Future Scenarios as a Tool for Collaboration in Forest Communities - Evans, K.; Jong, W. de; Cronkleton, P. (2008)
Forest devolution is meant to provide communities with greater decision-making power over the use and future of tropical forests. However, devolution policies have not always had the intended effect; in some cases they have caused or furthered the disenfranchisement of the poor, the creation of open access conditions, resource conflict and forest degradation. These problems are likely to arise when forest communities are at a disadvantage when interacting with other local players and are unprepared for their new opportunities and responsibilities due to their physical remoteness, cultural isolation, low literacy rates or lack of experience in formal planning and negotiation. This paper discusses how a participatory method to facilitate thinking about the future—called future scenarios—can help change the way forest communities and local governments interact. The paper reviews a growing body of literature on future scenarios and shares first-hand experiences with future scenarios in forest communities in the northern Bolivia Amazon and the central provinces of Vietnam. It finds that under the right conditions, the use of future scenarios allows forest communities to collaborate more effectively with local government, better assume responsibilities when given control over forests under devolution schemes and self-organize to benefit from the opportunities that communal control over forests offer. Future scenarios help communities think about dependency, vulnerabilities and ways to prepare for the future; the methods develop organizational capacity and encourage internal democratic processes and planning. Community leaders become more vocal and assertive in meetings with local government, and marginalized groups within communities, such as women or the poorest segments, make their voices heard. However, the methods are less effective when facilitation skills are not available or where government or other interests are threatened by local constituents, Future scenarios are not without their pitfalls and do not work in all situations, but given the appropriate context they can create “break-through moments” that improve collaboration between communities and local officials.